DISPLACEMENT OF TRIBES AND ITS IMPACT ON THEIR SOCIETY AND CULTURE IN JHARKHAND - Mahali, Samu (IJRDO - Journal of Social Science and Humanities Research, 2018)
The word displacement means the removal of something or people from its usual place or position by government which then occupies that place or position. Or displacement is the forcing of people away from the area or country where they live. “Jharkhand” literally means ‘the land of forests’ or ‘land of Tribes’ came into existence as 28th state of the Indian union on 15th of November, 2000 after a long mass struggle, which took place in the 20th century for the realization of a beautiful dream of the Adivasi heroes – Tilka Manjhi, Sidhu-Kanhu and Birsa Munda. The dream was to form exploitation free, humane and just Jharkhand, where the Adivasis can practice their ownership rights over the natural resources, enjoy autonomy and rule themselves as earlier they used to.As per the Census 2001, their total population in the state is 70,87,068 including 35,65,960 male and 35,21,108 female, which consists 26.3% of the total population (26,945,829) of the state though they were more than 50 percent before the independence of India. The growth of the Adivasi population is steadily declining. It was 17.3 per cent in 2001, which is lower by 6 per cent if compared with the growth (23.3 per cent) in 1991. The state has a total of thirty two (32) sub-communities of the Adivasis. Among them Santal, Oraon, Munda, Ho and Kharia are the major Adivasi groups in the state. The major Adivasi populations (91.7 percent) reside in villages and merely 8.3 percent have shifted to the urban areas. The rapid industrialization is one of the major reasons for population declination of the Adivasis.